In vitro antioxidant and, α-glucosidase inhibitory activities and comprehensive metabolite profiling of methanol extract and its fractions from Clinacanthus nutans - Alam, Md. Ariful; Sarker, Md. Zaidul Islam; Ghafoor, Kashif; Sahena, Ferdosh; Hakim, Md Abdul; Yusop, Nohd Rafii; Abir, H.M.; Bostanudin, Mo Fauzi; Perumal, Vikneswari; Khatib, Alfi (BioMed Central Ltd., 2017)
Background This study was aimed to evaluate antioxidant and α-glucosidase inhibitory activity, with a subsequent analysis of total phenolic and total flavonoid content of methanol extract and its derived fractions from Clinacanthus nutans accompanied by comprehensive phytochemical profiling.